2015
DOI: 10.1097/fpc.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

A pharmacogenetic candidate gene study of tenofovir-associated Fanconi syndrome

Abstract: BACKGROUND Tenofovir disoproxil fumarate (TDF) is a widely used antiretroviral agent with favorable efficacy, safety and tolerability profiles. However, renal adverse events, including rare Fanconi syndrome (FS), may occur in a small subset of HIV-infected treated patients. OBJECTIVES The aim of this study was to identify genetic variants that may associate with TDF-associated FS (TDF-FS). METHODS DNA samples collected from a 19 cases with TDF-FS and 36 matched controls were sequenced and genetic associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 46 publications
0
16
1
Order By: Relevance
“…showed that TFV was not substrate of MRP2 using transporter‐overexpressing cell lines. However, some gene association studies showed that ABCC2 variants were associated with TFV‐induced renal side effects in HIV‐infected patients . One patient had very high TFV‐DP CL in in our studied cohort (408% of the median), potentially driving the significance of this relationship; however, the effects of our significant SNPs on this parameter were independent.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…showed that TFV was not substrate of MRP2 using transporter‐overexpressing cell lines. However, some gene association studies showed that ABCC2 variants were associated with TFV‐induced renal side effects in HIV‐infected patients . One patient had very high TFV‐DP CL in in our studied cohort (408% of the median), potentially driving the significance of this relationship; however, the effects of our significant SNPs on this parameter were independent.…”
Section: Discussionmentioning
confidence: 63%
“…However, some gene association studies showed that ABCC2 variants were associated with TFV-induced renal side effects in HIV-infected patients. 44,45 One patient had very high TFV-DP CL in in our studied cohort (408% of the median), potentially driving the significance of this relationship; however, the effects of our significant SNPs on this parameter were independent. FTC-TP has higher CL out from the cells given an ABCC2_c.1249G>A variant, which increases MRP2 function.…”
Section: Clinical and Translational Sciencementioning
confidence: 79%
See 1 more Smart Citation
“…It is unclear why PRTD remained protracted in this case despite discontinuation of nucleotide analogues for more than one year. Rare variants in genes involved in the renal handling of nucleotide analogue may be associated with increased susceptibility to Fanconi's syndrome or overt PRTD [35]. Of note, the diagnosis of Fanconi's syndrome with a bicarbonate-loading test was not done to differentiate Fanconi's syndrome from overt RTD in this study.…”
Section: g0/mentioning
confidence: 80%
“…The most serious complication linked with nucleotide analogue therapy is Fanconi syndrome, a drug‐induced form of severe renal tubular damage. Fanconi syndrome is characterized by profound (but reversible) hypophosphatemia, normoglycemic glycosuria, and nonalbumin proteinuria …”
Section: Introductionmentioning
confidence: 99%